Genetic evidence for species cohesion, substructure and hybrids in spruce. Issue 8 (10th April 2019) - Haselhorst, Monia S. H.; Parchman, Thomas L.; Buerkle, C. Alex
Abstract: The origin and history of species are shaped by various evolutionary dynamics, including their persistence in the face of potential gene flow from related taxa. In this study, we use broad geographical and taxonomic sampling (2, 219 individuals) to establish the distribution of species, hybrids and cryptic genetic variation within the conifer genus Picea (spruce) across western North America. We demonstrate that the six species of spruce in this region are distinguishable based on their genetic composition, and that the more closely related Engelmann spruce ( P. engelmannii ) and white spruce ( P. glauca ) have generated numerous and widespread hybrids. These hybrids occur in the central Rocky Mountains, well to the south of the well‐established region of admixture in Canada. Additionally, we provide evidence for subdivision within Engelmann spruce, manifested as a southern Rocky Mountains form, and a northern Rocky Mountain and Cascade mountains (western) form. In the intervening central Rocky Mountains region (forests in Wyoming and adjacent states) we found primarily individuals with admixed ancestry. Following their origin, these species of spruce have interacted repeatedly and in different geographical contexts. Multiple pairs of species have been shown to hybridize, yet the species persist and retain distinguishable compositions. At the same time, large geographical areas exist where hybrids are pervasive. Consequently, spruce provide a case study for the maintenance of species boundaries, particularly for how widespread hybridization need not lead to the collapse and loss of species.